An Appraisal of Adaptation Measures to Climate Variability by Smallholder Irish Potato Farmers in South Western Uganda - Mugagga, Frank; Nimusiima, Alex; Elepu, Julius (American Journal of Climate Change, 2020)
Climate change and variability are a reality and have had marked effects on both human and ecological systems. Adaptation to such effects either directly or indirectly is viewed as a novel way of reducing the spread of the associated risks. The study was conducted in Rubanda District with a general aim of evaluating the effectiveness of adaptation measures to climate variability used by smallholder Irish potatoes farmers. Specifically, we sought to appraise smallholder Irish potato farmers’ perceptions about the effectiveness of climate variability adaptation measures and implications on Irish potato productivity. We undertook a cross-sectional study to collect data from total of 197 farmers using a structured questionnaire. Other participatory methods such as focus group discussions and key informant interview were also used to complement the household survey. Data were analyzed using SPSS Version 23 to generate descriptive statistics as well as relationships between the adaptation measures and the productivity of the Irish potatoes using a Cobb-Douglas production function. The Cobb-Douglas model revealed that the use of fertilizers was significantly and positively associated with productivity of Irish potato (P < 0.001). Furthermore, Smallholder Irish potato farmers perceived the use of technology, terracing, early planting and application of fertilizers as the most effective climate variability adaptation measures. The study recommends that measures that are cost-effective, efficient and coherent should be promoted to offset the impacts of climate variability which would include the adoption of improved potato varieties and use of fertilizers with proper management of erosion. Off-season planting of Irish potatoes in the wetlands should be discouraged by the local administration and the National Environment Management Authority. This calls for a collective action involving the agricultural practitioners and inline civil society organizations to ensure that farmers have access to such inputs.
Keywords: Adaptation Measures; Climate Variability; Efficacy; Irish Potato Farmers; South Western Uganda